グローバル ジシンガク ニ オケル キョクイキ ケンキュウ ノ ゲンジョウ ト ショウライ テンボウ ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 金尾, 政紀; カナオ, マサキ; Kanao, Masaki (2004)
P(論文) 「グローバル地震学における極域研究の現状と将来展望に関する研究小集会」を2003年1月23日24日に国立極地研究所で開催した.参加者は所内外合わせて計38名であった.本集会では,地震学的各種手法による1)両極域をターゲットとした地域的局所的な空間スケールでの研究,2)極域のデータを利用した汎地球スケールでの研究,及び3)ゴンドワナ超大陸群や北極圏ヒマラヤ等での研究,等の成果発表と議論を行った.これにより,グローバル地震学研究を補う上で必要な領域の一つである極域の重要性について再認識を行い,今後の研究指針について意見交換を行った.また,ゴンドワナ超大陸の形成分裂過程,プルームテクトニクスや氷床変動地殻変動,さらに高温高圧による岩石の弾性波速度実験等の様々な学際的検討と,今後のデータアーカイブ観測技術研究方法の将来展望についても議論した. A workshop on Present status and future plans of polar studies in global seismology" was held on 23rd and 24th January 2003, at the National Institute of Polar Research with 38 participants. The purposes of this workshop were to discuss scientific work by several seismological methods for more efficient scientific planning and insights. The presentations were divided into the three sessions 1) regional and local studies to target the polar regions, 2) global studies by use of data from polar regions, and 3) studies in the Arctic, high mountains such as the Himalaya, and in several continental blocks in a past super-continent: Gondwana. From this workshop, we could identify the significance of polar studies for global seismology; in particular, insight into the inner structure and dynamics of the Earth from special windows located at high latitude. We have also conducted several multidisciplinary studies such as amalgamation and breakup of the super-continent, plume tectonics, ice sheet dynamics and crustal movements, and laboratory seismic velocity measurements of the metamorphic rocks. Moreover, we have held fruitful discussions about future plans for data archiving technology, observation systems, and methodology for seismological analyses. departmental bulletin paper